SOSIALISASI GIZI SEIMBANG DAN DETEKSI DINI KESEHATAN KADAR GULA DARAH, KOLESTROL TOTAL DAN ASAM URAT DI DUSUN KEBONDUREN - Andri Wahyu Utomo; Firya Huwaida Irbah; Wisnu Juania Indriani; Sukma Heni Martiningsih; Berril Imsi Qi Nora (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
The most important principle of the Tri Darma of Higher Education in relation to the social and cultural environment of society is called community service. The existence of input for improving the quality of Higher Education in the community which is needed is expected by establishing good and sustainable relations between Higher Education and the community. On January 16, 2023, a Community Service Activity was held to promote Balanced Nutrition and Early Health Detection of Blood Sugar, Total Cholesterol and Uric Acid Levels in Kebunduren Hamlet. Prior to the start of the project, there was still very little public awareness of anemia, hypertension, diabetes, gout, and cholesterol. Health Check-ups for the residents of Kebunduren Hamlet, Kenongorejo Village, Pilangkenceng District, totaled 35 people consisting of 1 male and 29 women.